The immunogenicity of recombinant vaccines based on modified Vaccinia Ankara (MVA) viruses expressing African horse sickness virus VP2 antigens depends on the levels of expressed VP2 protein delivered to the host - Calvo-Pinilla, Eva; Gubbins, Simon; Mertens, Peter P.C.; Ortego, Javier; Castillo-Olivares, Javier (Elsevier, 2018)
African horse sickness (AHS) is a lethal equine disease transmitted by Culicoides biting midges and caused by African horse sickness virus (AHSV). AHS is endemic to sub-Saharan Africa, but devastating outbreaks have been recorded periodically outside this region. The perceived risk of an AHS outbreak occurring in Europe has increased following the frequent epidemics caused in ruminants by bluetongue virus, closely related to AHSV.